2023
DOI: 10.2196/48581
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis Disclosure and Peer-to-Peer Information Seeking Among COVID-19–Infected Social Media Users: Survey of US-Based Adults

Stephen Neely,
Feng Hao

Abstract: Background Research examining online health communities suggests that individuals affected by chronic health conditions can obtain valuable information and social support through participation in peer-to-peer web-based information exchanges, including information sharing and seeking behaviors. The risks and rewards of these same behaviors in the case of acute illnesses, such as COVID-19, are less well understood, though there is reason to believe that individuals with COVID-19 and other acute illne… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The World Health Organization (WHO) noted in September 2020 that COVID-19 “is the first pandemic in history in which technology and social media are being used on a massive scale to keep people safe, informed, productive and connected” [ 22 ]. While social media have been shown to provide some important benefits, particularly for those actively infected with the SARS-CoV-2 virus [ 23 ], evidence also shows that platforms such as Facebook and Twitter have contributed to the politicization of COVID-19, as well as the viral spread of misinformation. As a result, health professionals have been forced to learn and innovate in real-time to combat the evolving challenges and threats associated with the digital infodemic .…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) noted in September 2020 that COVID-19 “is the first pandemic in history in which technology and social media are being used on a massive scale to keep people safe, informed, productive and connected” [ 22 ]. While social media have been shown to provide some important benefits, particularly for those actively infected with the SARS-CoV-2 virus [ 23 ], evidence also shows that platforms such as Facebook and Twitter have contributed to the politicization of COVID-19, as well as the viral spread of misinformation. As a result, health professionals have been forced to learn and innovate in real-time to combat the evolving challenges and threats associated with the digital infodemic .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence collected across a range of geographical contexts showed heavy use of these platforms for information seeking during the COVID-19 pandemic [ 1 - 3 ], and health professionals have increasingly sought to engage with SNS users through these mediums in an attempt to promote timely and reliable health guidance [ 4 , 5 ]. On the one hand, these tools promise greater access and connectivity for patients and consumers, and recent evidence has suggested that individuals infected with COVID-19 were able to gain valuable information and social support through engagement with their SNS communities during the pandemic [ 6 ]. On the other hand, social networking platforms such as X have proven highly susceptible to misinformation and politicization, particularly as it relates to the safety and efficacy of vaccines [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%